The Effect Of Sales Promotion And Customer Satisfaction On Repeat Purchase Interest At Ferda Purwasari Wholesale Store, Karawang Regency - Mohammad Ferda Aji Perdana; Citra Savitri; Syifa Pramudita Faddila (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This study sought to determine how customer satisfaction and sales promotion factors affected consumers' interest in making another purchase at Toko Grosir Ferda. Research method— The research methodology employed a quantitative approach using a survey method. The population was all Toko Grosir Ferda customers for a month, and the sample of 130 respondents was selected using the accidental sampling technique. Result The study's findings suggest that repurchase intention is significantly influenced by customer satisfaction and sales promotion. Conclusion— The research's implications include the need for a strategy to improve customer service and sales promotion in order to boost customer loyalty and repurchase interest in the future. Social media implementation is also anticipated in order to keep Toko Grosir Ferda competitive in raising customer satisfaction levels.